2019
DOI: 10.11114/aef.v6i2.3867
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Capital Structure on the Profitability of Publicly Traded Manufacturing Firms in Bangladesh

Abstract: This research explores the impact of capital structure on the profitability of publicly traded manufacturing firms in Bangladesh. In this paper, we applied the fixed effect regression to find out the correlation among independent variables (debt ratio, equity ratio and debt to equity ratio) and dependent variables (return on asset, return on equity and earnings per share). A sample of 50 observations of selected 10 manufacturing companies listed in Dhaka Stock Exchange has been analyzed over the period of 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 7 publications
5
11
0
11
Order By: Relevance
“…Our statistical findings based on the capital structure and ROE are in line with Nguyen and Nguyen's (2020) study in Vietnam. Rahman et al. 's (2019) debt to equity ratio findings show a significant negative impact on the ROE in Bangladesh and are in line with the current study's outcomes.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our statistical findings based on the capital structure and ROE are in line with Nguyen and Nguyen's (2020) study in Vietnam. Rahman et al. 's (2019) debt to equity ratio findings show a significant negative impact on the ROE in Bangladesh and are in line with the current study's outcomes.…”
Section: Resultssupporting
confidence: 91%
“… Rahman et al. (2019) explored the effect of the capital structure on the profitability of publicly traded manufacturing firms in Bangladesh.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study noticed that debt ratio has negative effect on ROA, debt equity ratio has a negative impact on ROE, and size is positively linked with ROE. However, in a recent study conducted on 10 firms listed in Dhaka stock exchange from the period of 2013 to 2017 by Rahman et al (2019) who found that debt ratio and equity ratio have positive impact on ROA, while they found that debt to equity has negative impact on ROA.…”
Section: Literature Reviewmentioning
confidence: 94%
“…The system of the banking structure in Iraq is divided into four groups, such as public banks, survive without capital and these capitals come from different sources, such as debts and equity. Muhammad et al (2014), Pinto et al (2017), Mouna et al (2017), Musah (2017), Mehar (2018) and Rahman et al (2019) believe that an important decision in each financial institution is capital structure. For instance, Tanni (2013) believes that a major topic in finance nowadays is capital structure.…”
Section: Introductionmentioning
confidence: 99%
“…Greater proportion of debt is preferred by investors in a country where debt interest is tax deductible. Firms use a mix of debt and equity in various proportions in order to maximize the overall market value of the firm (Rahman, Sarker & Uddin, 2019).…”
Section: Literature Review 21 Capital Structurementioning
confidence: 99%